2015
DOI: 10.1002/jso.23855
|View full text |Cite
|
Sign up to set email alerts
|

Log odds of positive lymph nodes as a prognostic indicator in stage IV colorectal cancer patients undergoing curative resection

Abstract: The LODDS is a good prognostic indicator in Stage IV CRC patients who have undergone curative resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 36 publications
0
25
0
Order By: Relevance
“…For this reason, it is intuitive that RLNs and the number of negative lymph nodes should be simultaneously taken into consideration when formulating an adjuvant treatment plan. LODDS is an intuitive indicator that is reflective of both interrogated lymph nodes and the number of negative lymph nodes, and its use is supported by available data in other malignancies [7, 911]. For the first time in the epithelial ovarian cancer population, we evaluated ROC curves based on RLNs, PLNs, LNR and LODDS, and found that LODDS has the highest AUC with superior sensitivity and specificity compared to other factors.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…For this reason, it is intuitive that RLNs and the number of negative lymph nodes should be simultaneously taken into consideration when formulating an adjuvant treatment plan. LODDS is an intuitive indicator that is reflective of both interrogated lymph nodes and the number of negative lymph nodes, and its use is supported by available data in other malignancies [7, 911]. For the first time in the epithelial ovarian cancer population, we evaluated ROC curves based on RLNs, PLNs, LNR and LODDS, and found that LODDS has the highest AUC with superior sensitivity and specificity compared to other factors.…”
Section: Discussionmentioning
confidence: 94%
“…Recently, ratio of PLNs to RLNs (LNR) and log of odds between PLNs and the number of negative lymph node (LODDS) have emerged as alternative predictive factors for outcomes in breast [6, 7], gastric [8], pancreatic [9] and colorectal cancer [10, 11]. LNR is defined as the ratio of PLNs to RLNs.…”
Section: Introductionmentioning
confidence: 99%
“…Median follow up was 16 months (range, 0-117 months). The median LNR was 0.25 (range, 0-0.94) and used a cutoff to define patients with a low LNR (L-LNR, ≤0.25) or high LNR (H-LNR, >0.25), as previously reported (8). Among 53 eligible patients, 26 (49%) had H-LNR.…”
Section: Resultsmentioning
confidence: 99%
“…Appropriate surgical technique along with diligent pathologic examination of resected specimen are required to consistently attain that goal (16,17). Due to variability in surgical technique and pathologic assessment of specimens, recent studies have proposed alternative LN parameters which may be more reliable than standard nodal staging in predicting outcomes (8,9). The most thoroughly investigated alternative nodal staging approach is LNR (18,19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation